The Performance of Pesantren as Islamic Education A Case Study - Djamaluddin Perawironegoro; Wantini Wantini; Ridha Makky; Muhammad Irfanuddin Kurniawan (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The article aims to describe and analyze the performance of Pesantren as Islamic educational institution. The research conducted at Pesantren Darunnajah 2 Cipining. The method used by researchers for answering the research question is a case study method with qualitative approach. The data collection technique was the interview, observation, and documentation. Than the analysis technique used through stages, they are data collection, data reduction, data classification, and conclusion withdrawal. Pesantren performance is a process and the result as cummulative process of the performance of teachers and administrators, as individuals and the units. Teacher’ performance was the process and result of teachers’ works related to teaching, self-learning, and managing the boarding units. Unit performance is the process and the result of teachers’ jobs according to the functions and objectives of the units, to achieve the vision and mission of Pesantren. Pesantren performance indicators were known by it relation to the performance of education and instruction, facilities and infrastructure development, internalization of values, and Pesantren philosophy. The acquaintance of the performance of Pesantren had an impact on the improvement and sustainable development of Pesantren.to be guidelines for assessment and development Based on findings, the performance of pesantren as Islamic education is contain of the performance of units, teachers, and administrator. To measure the performance of the pesantren can be done by indicators; the teaching and learning process, teachers self learning, and managing units of pesantren. The performance of pesantren is shown by improving teaching and learning processes and outcomes, developing facilities and infrastructure, and internalizing the values and philosophy of pesantren.